Future Sea Level Change Under Coupled Model Intercomparison Project Phase 5 and Phase 6 Scenarios From the Greenland and Antarctic Ice Sheets. Issue 16 (19th August 2021) - Payne, Antony J.; Nowicki, Sophie; Abe‐Ouchi, Ayako; Agosta, Cécile; Alexander, Patrick; Albrecht, Torsten; Asay‐Davis, Xylar; Aschwanden, Andy; Barthel, Alice; Bracegirdle, Thomas J.; Calov, Reinhard; Chambers, Christopher; et al.
Abstract: Projections of the sea level contribution from the Greenland and Antarctic ice sheets (GrIS and AIS) rely on atmospheric and oceanic drivers obtained from climate models. The Earth System Models participating in the Coupled Model Intercomparison Project phase 6 (CMIP6) generally project greater future warming compared with the previous Coupled Model Intercomparison Project phase 5 (CMIP5) effort. Here we use four CMIP6 models and a selection of CMIP5 models to force multiple ice sheet models as part of the Ice Sheet Model Intercomparison Project for CMIP6 (ISMIP6). We find that the projected sea level contribution at 2100 from the ice sheet model ensemble under the CMIP6 scenarios falls within the CMIP5 range for the Antarctic ice sheet but is significantly increased for Greenland. Warmer atmosphere in CMIP6 models results in higher Greenland mass loss due to surface melt. For Antarctica, CMIP6 forcing is similar to CMIP5 and mass gain from increased snowfall counteracts increased loss due to ocean warming. Plain Language Summary: The melting of the Greenland and Antarctic ice sheets (GrIS and AIS) will result in higher sea level in the future. How sea level will change depends in part on how the atmosphere and ocean warm and how this affects the ice sheets. We use multiple ice sheet models to estimate possible future sea levels under climate scenarios from the models participating in the new Coupled Model Intercomparison Project phase 6 (CMIP6), which generally indicate a warmer world that the previous effort (CMIP5). Our results show that the possible future sea level change due Antarctica is similar for CMIP5 and CMIP6, but the warmer atmosphere in CMIP6 models leads to higher sea‐level contributions from Greenland by the end of the century. Key Points: We compare results from an ice sheet model inter‐comparison forced using Coupled Model Intercomparison Project phase 6 and phase 5 climate projections Projected sea level at 2100 is higher for Greenland under CMIP6 scenarios than CMIP5, but similar for Antarctica under both scenarios CMIP6 warmer climate results in increased Greenland surface melt while increased snowfall mitigates loss from ocean warming for Antarctica